Nasal Septum Changes in Adolescents Treated with Tooth-Borne and Bone-Borne Rapid Maxillary Expansion: A CBCT Retrospective Study Using Skeletal Tortuosity Ratio and Deviation Analysis - Vincenzo Ronsivalle; Elisabetta Carli; Antonino Lo Giudice; Manuel Lagravère; Rosalia Leonardi; Pietro Venezia (MDPI AG, 2022)
Background: Using three-dimensional (3D) images, this study evaluated the impact of Rapid Maxillary Expansion (RME) on changes in Nasal Septal Deviation (NSD). Methods: Cone-beam computed tomography (CBCT) scan of 40 children with transverse maxillary deficiency, who received tooth-borne (TB) RME or bone-borne (BB) RME, were included in this investigation. Two CBCT scans were performed: one before to appliance installation (T0) and one after a 6-month retention period (T1). The analysis was performed by dividing the actual length of the septum by the desired length in the mid-sagittal plane to measure NSD based on the tortuosity ratio (TR). Results: Subjects in the TB group showed a statistically significant reduction (p < 0.05) of the TR value from T0 to T1, according to the paired Student t test. Subjects in the BB group showed similar findings, with a statistically significant reduction (p < 0.05) of the TR value from T0. No statistically significant differences were found between the mean changes of TR between TB group and BB group. Conclusions: RME may have some effects in reducing the degree of NSD; however, no differences were found between RME performed with TB and BB anchorage systems.